SISTEM PENGENDALIAN INTERNAL PENGELOLAAN ASET BERSEJARAH DI KABUPATEN SEMARANG (Studi Kasus Pada Pengelolaan Candi Gedongsongo) - Ruci Abdi Muhyi; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2021)
This study aims to determine and understand how the internal control system applied to heritage asset, not many researchers have discussed the internal control of heritage asset, especially in the daily management of heritage asset, researchers have different opinions about whether heritage asset are assets or liabilities. This study uses a case study on the management of Gedongsongo Temple. The internal control system is very important because by having a good system, the agency is able to carry out its daily activities efficiently and effectively, so as to prevent any problems that will occur. The results of this study will show whether the performance of the Gedongsongo Temple manager is in accordance with Government Regulation No. 60 of 2008 concerning Internal Control Systems and Law No. 11 of 2010 concerning Cultural Heritage Management.This study uses primary data in the form of interviews and secondary data in the form of literature references and data from journals, books, and documents published by related agencies or agencies, including the Central Java Province Cultural Heritage Conservation Center and the Semarang Regency Tourism Office. In addition, in data collection, this study uses the method of observation, documentation and interviews. Meanwhile, for data analysis, this study used data reduction, data presentation, drawing conclusions and verification. Data validity testing was also used in this study to strengthen the data obtained.The results showed that Gedongsongo Temple is managed by 3 institutions, namely the Central Java BPCB which is responsible for management, maintenance and preservation, the Semarang Regency Tourism Office has the authority to promote and develop tourist areas, while Perum Perhutani is responsible for the preservation of protected forest areas in the Gedongsongo Temple Area. .The research results also show that the Central Java BPCB recognizes Gedongsongo Temple as a historical asset and as a cultural heritage that must be preserved, protected, and preserved so that it can be passed on to the next generation. Finally, the research results show that the management of Gedongsongo Temple is in accordance with Government Regulation No. 60 of 2008.